HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN GEJALA DEPRESI PADA REMAJA DI SMAN 3 DENPASAR - Gusti Ayu Sabila Prajaniti; Kadek Eka Swedarma; Meril Valentine Manangkot (Coping: Community of Publishing in Nursing, 2022)
Teenagers now use social media on a daily basis. However, excessive social media use can have a negative impact on adolescent mental health, including depression. The purpose of this study is to determine the relationship between social media use and depression symptoms in adolescents at SMAN 3 Denpasar. This study employs a descriptive correlative research design with a cross-sectional approach. Respondents in this study were 188 teenagers from class XI who majored in science and social studies and were chosen using a proportional random sampling technique. The Bergen Social Media Addiction Scale (BSMAS) questionnaire was used to collect data on social media use, and the Beck Depression Inventory (BDI) questionnaire was used to collect data on depression symptoms. According to the findings of the univariate analysis, the majority of the adolescents experienced normal stages of social media use (94 adolescents (50.0 percent)) as well as normal depressive symptoms (96 adolescents) (51.1 percent). The Spearman Rank test was used for bivariate analysis, which revealed a significant but weak relationship between social media use and depression symptoms (p value = 0.001; r = 0.235). The findings of this study point to a positive relationship, implying that the more adolescents use social media, the more symptoms of depression they experience. This study is expected to provide adolescents with information about the impact of social media use on adolescent mental health, so that adolescents can pay attention to their use of social media as needed.